Analisis Sosio-Yuridis Terkait Pelaksanaaan Peraturan Perundang – Undangan atau Kebijakan Hukum Terhadap Pelayanan Rawatan Intensif Rumah Sakit di Kota Batam Tahun 2019 - Fajri Israq (Universitas Internasional Batam, 2021)
In the health service system, the hospital acts as a referral place and a further health service facility. The refusal of admission of patients with intensive care at the hospital, accompanied by efforts to avoid the provision of facilities and facilities from the hospital for ICU treatment, appeared in several hospitals. Even though the role of the hospital itself as a place for further treatment of primary care is so big and important. This also contradicts the main duties and functions of the hospital itself, although it still pays attention to the class of the hospital itself. There is a legal or policy conflict in the application of ICU services, between Law number 44 of 2009 concerning Hospitals, Minister of Health Regulations number 1778 of 2010 concerning guidelines for intensive care services, and Law number 24 of 2011 concerning BPJS. The ineffective application of the law is seen from the 5 factors of legal effectiveness theory described by Soerjono Soekanto, namely the legal factors themselves, law enforcers, facilities or facilities, society and culture. The implementation of Minister of Health Regulations number 1778/2010 and Law number 44/2009 on ICU tends to run less effectively, so there are still many cases of rejection of ICU admission. At the end of the study, it was found that there was a need to expalin legal / regulatory oversight of Minister of Health Regulations number 1778/2010 and Law number 44/2009 strengthening of laws / policies to become the legal basis for health services.